2020
DOI: 10.1021/acsomega.0c02580
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Injectable Chitosan/Collagen/β-Glycerophosphate Composite Hydrogels for Enhancing Wound Healing by Encapsulating Mesenchymal Stem Cell Spheroids

Abstract: Chronic wounds caused by diabetic or venous diseases remain a social and healthcare burden. In this work, a new strategy is proposed in which injectable thermosensitive chitosan/collagen/β-glycerophosphate (β-GP) hydrogels were combined with three-dimensional mesenchymal stem cell (3D MSC) spheroids to accelerate chronic wound healing by enhanced vascularization and paracrine effects. Chitosan/collagen/β-GP solution mixed with 3D MSC spheroids was rapidly transformed to a gel at body temperature by physical cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…It has been reported that chitosan-poly(vinyl alcohol) hydrogels loaded with SNAP can promote angiogenesis [ 14 ]. In addition, mesenchymal stem cells cultured in 3D hydrogels accelerated wound healing through enhanced vascularization and paracrine effects in wounds [ 24 ]. The higher wound healing efficiency of the 3D cell matrix may be caused by the higher survival rate of stem cells and the hypoxic environment in the 3D constructs [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that chitosan-poly(vinyl alcohol) hydrogels loaded with SNAP can promote angiogenesis [ 14 ]. In addition, mesenchymal stem cells cultured in 3D hydrogels accelerated wound healing through enhanced vascularization and paracrine effects in wounds [ 24 ]. The higher wound healing efficiency of the 3D cell matrix may be caused by the higher survival rate of stem cells and the hypoxic environment in the 3D constructs [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, culturing cells in a 3D construct is more suitable for simulating the microenvironment and subsequently influencing behaviour and gene expression [ 23 ]. Recent studies have intended to improve stem cell retention at wound sites by using spheroids, hydrogel systems, and biological scaffolds [ 24–26 ]. At present, few studies have focussed on the combination of stem cells and nitric oxide (NO) in 3D bioscaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…This biomatrix showed to exert an excellent therapeutic effect compared to other control groups. This technique was then examined by the elevation of cells attachment and proliferation for further investigation for the future use of chronic and venous wound management [ 64 ].…”
Section: Development Of Injectable Hydrogel For Diabetic Foot Managementmentioning
confidence: 99%
“…In response to this, nowadays, personalizable bioengineered wound dressings and bio-fabrication techniques are being extensively developed. New research in chronic wound healing presents an innovative therapeutic strategy by using three-dimensional (3-D) hydrogel-based materials with superior therapeutic potential [3,4]. Hydrogel-based chronic wound dressings exhibit multifunctional properties, such as biodegradability, biocompatibility, sustained diffusion of bioactive molecules, high cell/drug embedding rate, pore structure, and appropriate mechanical strength [5].…”
Section: Introductionmentioning
confidence: 99%